Simfoni Kebhinekaan: Menggagas Peran Musik dalam Memperkuat Persatuan Bangsa Berlandaskan Nilai-Nilai Pancasila - Maria Armalita Tumimbang; Riandli Saliareng (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
This research aims to examine the role of music in strengthening national unity based on the values ​​of Pancasila. The approach used is descriptive qualitative with the aim of deepening the understanding of the relationship between music and Pancasila values ​​and their impact in building unity and integrity in society. This research involves analysis of music theory, Pancasila concepts, as well as case studies to illustrate the relationship between the two. First of all, this research describes the concept of diversity and Pancasila values ​​as a philosophical basis for understanding the unity of the Indonesian nation. Values ​​such as belief in the Almighty God, just and civilized humanity, Indonesian unity, democracy led by wisdom in deliberation/representation, and social justice for all Indonesian people are the basis for maintaining diversity and strengthening unity. This research explores the role of music in reflecting Pancasila values ​​and facilitating social integration among diverse communities. Music as a medium for artistic expression has the power to convey messages of diversity, tolerance and unity through its lyrics, melodies and artistic performances. Case studies will show how various musical genres, such as traditional music, pop, rock, etc., can unite various social groups and dissolve cultural and religious differences. In addition, this research will discuss the practical impact of implementing Pancasila values ​​in the music industry and music education in Indonesia. By strengthening understanding of Pancasila values ​​in musical works and conveying positive messages, music can be an effective means of strengthening ties of brotherhood among Indonesian people. Other strategies that can be developed in this context include the use of music in formal and informal educational programs aimed at fostering a spirit of nationalism, tolerance and social justice. In conclusion, this research shows that music has great potential as a tool to strengthen national unity based on the values ​​of Pancasila. With a deeper understanding of the relationship between music and national values, we can develop more effective strategies in promoting harmony and solidarity amidst the diversity of Indonesian society.